MENINGKATKAN HASIL BELAJAR SISWA PADA SUB TEMA II PENTINGNGYA MAKANAN SEHAT BAGI TUBUH DENGAN MENGGUNAKAN METODE MIND MAPPING DI KELAS V SDN 100308 PANOMPUAN - Nasution, Angela; Nasution, Sartika Rati Asmara; Ningtyas, Rani Kusuma; Sucahyo, Eko (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This study aims to improve student learning outcomes in science learning outcomes in science learning in class V of SD Negeri 100308 Panompuan East Angkola sub-district. This type of research is classroom action research (PTK) consist of two cycles which include planning, action, observing and reflection. The subject were 23 fifth grade student at SD Negeri 100308 Panompuan, East Angkola District. Data collection tekchinques throught activity sheets and test sheest. Based on the observer’s observations, teacher and student activity increased in each cycle. In cycle I the teacher’s aktivities score of 65,62% and in cyle II it was 85,93%. While student avtivities in cycle I obtained an average score of 64,28% and cycle II was 89,28%. In learning cycle I to cycle II there was an increase in student learning outcomes. The value of student learning in cycle I was an average of 74,78% and in cycle II there was an increase in student learning outcomes with an average value of 85,21%. The result of this research show that the mind mapping method can improve student learning outcomes.